2021
DOI: 10.1177/20543581211046078
|View full text |Cite
|
Sign up to set email alerts
|

Patient, Caregiver, and Provider Perspectives on Improving Information Delivery in Hemodialysis: A Qualitative Study

Abstract: Background: Patients with kidney failure are exposed to a surfeit of new information about their disease and treatment, often resulting in ineffective communication between patients and providers. Improving the amount, timing, and individualization of information received has been identified as a priority in in-center hemodialysis care. Objective: To describe and explicate patient, caregiver, and health care provider perspectives regarding challenges and solutions to information transfer in clinical hemodialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In the case of the latter, information is broken down into smaller "chunks" and reviewed over multiple sessions. 29 This is supported by a qualitative study, by Ferreira da Silva et al, 31 which analyzed interview data of patients from 5 Canadian hemodialysis centers receiving in-center hemodialysis, their caregivers, and health providers. The researchers explored the barriers and solutions to delivery of information related to hemodialysis and identified patients felt overwhelmed with the amount of information they received when first initiating hemodialysis which made it difficult to retain.…”
Section: Discussionmentioning
confidence: 94%
“…In the case of the latter, information is broken down into smaller "chunks" and reviewed over multiple sessions. 29 This is supported by a qualitative study, by Ferreira da Silva et al, 31 which analyzed interview data of patients from 5 Canadian hemodialysis centers receiving in-center hemodialysis, their caregivers, and health providers. The researchers explored the barriers and solutions to delivery of information related to hemodialysis and identified patients felt overwhelmed with the amount of information they received when first initiating hemodialysis which made it difficult to retain.…”
Section: Discussionmentioning
confidence: 94%
“…Participants were offered alternative interview formats, and those wishing to proceed may have chosen this format for their own comfort or convenience. Other studies have used similar interview approaches during hemodialysis without compromising data quality [ 49 , 60 , 61 ]. Future research should explore the implications of PROM use for caregivers, application of the study’s PROM resources outside of the hemodialysis setting (e.g., with patients’ primary care physicians), and preferences for and influence of different PROM types on interdisciplinary hemodialysis care.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that peer support can be given to and is valued by people who present late to RRT. People often feel overwhelmed when commencing dialysis, even when planned and controlled [10], and when setting up this trial there were concerns that late presenters would feel too overwhelmed or physically unwell to welcome or bene t from peer support. However, acceptability, de ned as 'the extent to which people receiving a healthcare intervention consider it to be appropriate, based on anticipated or experienced cognitive and emotional responses to the intervention' [24], has been demonstrated: consent rates were high and patient-reported measures encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…Peer support -the provision of informational and emotional support by people with experience of kidney disease to others sharing the condition -might be one such intervention. Late-presenters feel overwhelmed and struggle to take in complex new information; although both NICE and UK Renal Association guidelines emphasise how important education and decision support is for late-presenters [1,2] many renal teams lack time and skills to educate optimally [10]. Peer supporters offer information about living with kidney disease which is jargon-free and at a level easily understood by lay-people [11], potentially providing a valuable adjunct to standard education.…”
Section: Introductionmentioning
confidence: 99%